1985
DOI: 10.1111/j.1095-8649.1985.tb04013.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestive enzyme pattern of two stomachless filter feeders, silver carp, Hypophthalmichthys molitrix Val., and bighead carp, Aristichthys nobilis Rich.

Abstract: Activities of digestive enzymes (trypsin and amylase) of microplanktophagous silver carp, Hypophthalmichthys molitrix, and macroplanktophagous bighead carp, Aristichthys nobilis, were investigated in relation to pH in 10 different segments of the gut. In addition, the possible existence of 'classical' lysozyme in both species and cellulase in silver carp were scrutinized, but no activities were detected. Tryptic and amylolytic activities decreased sharply from fore-gut to hind-gut indicating an efficient reabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 32 publications
2
44
0
2
Order By: Relevance
“…Lazzaro, 1987 . Although phytoplankton are considered to be the major nutritional component of many filter-feeding fishes, the digestibility of algae has been a matter of debate for Ž decades, i.e., gut content comparison between fore-gut and hind-gut Ni and Chiang, . Ž 1954;Spataru, 1977;Bitterlich, 1985a and analysis of digestive enzyme Bitterlich, . 1985b,c show that it is rather difficult for silver carp to digest algae with cellulose cell wall, while studies by using isotope techniques indicates that this fish digests green Ž algae and cyanobacteria efficiently Iwata, 1976;Shi et al, 1976;Zhu, 1982;Zhu and .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lazzaro, 1987 . Although phytoplankton are considered to be the major nutritional component of many filter-feeding fishes, the digestibility of algae has been a matter of debate for Ž decades, i.e., gut content comparison between fore-gut and hind-gut Ni and Chiang, . Ž 1954;Spataru, 1977;Bitterlich, 1985a and analysis of digestive enzyme Bitterlich, . 1985b,c show that it is rather difficult for silver carp to digest algae with cellulose cell wall, while studies by using isotope techniques indicates that this fish digests green Ž algae and cyanobacteria efficiently Iwata, 1976;Shi et al, 1976;Zhu, 1982;Zhu and .…”
Section: Introductionmentioning
confidence: 99%
“…However, in stomachless filter-feeding fishes such as silver carp, the pH of the gut fluids is usually ) 6. The lack of cellulase in the gut fluids also indicates that it is difficult for them to Ž breakdown cellulose cell walls by enzymatic digestion Ni and Chiang, 1954;Bitterlich, . 1985a .…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies on the glycogen content estimated by many authors [11][12][13][14][15]. Digestive enzyme pattern of two stomachless filter feeders, silver carp, Hypophthalmichthys molitrix Val., and bighead carp, Aristichthys nobilis has been reported [41]. Influence of Bacillus coagulans CC1 on growth performance and digestive enzyme activites of Catla catla had been reported [42].…”
Section: Discussionmentioning
confidence: 99%
“…In filter-feeding fish with no stomachs, such as silver carp, the pH of the gut fluids usually is >6. No cellulase in the gut of silver carp was found [26], and in vitro incubation of a filamentous cyanobacterium (Anabaena flos-aquae) with digestive juices of silver carp resulted in only 10% of the algal protein being hydrolyzed to free amino acids [24]. It was concluded that silver carp are omnivorous rather than herbivorous [25,26].…”
Section: Digestion Of Cyanobacteria By Silver and Bighead Carpmentioning
confidence: 99%